Analyzing the Role of Repolarization Gradients in Post-infarct Ventricular Tachycardia Dynamics Using Patient-Specific Computational Heart Models - Sung, Eric; Prakosa, Adityo; Trayanova, Natalia A. (Frontiers in Physiology, 2021)
Aims: Disease-induced repolarization heterogeneity in infarcted myocardium contributes to VT arrhythmogenesis but how apicobasal and transmural repolarization gradients additionally affect post-infarct VT dynamics is unknown. The goal of this study is to assess how apicobasal and transmural repolarization gradients impact post-infarct VT dynamics using patient-specific heart models. Method: 3D late-gadolinium enhanced cardiac magnetic resonance images were acquired from 7 post-infarct patients. Models representing the patient-specific scar and infarct border zone distributions were reconstructed without (baseline) and with repolarization gradients along both the apicobasal and transmural axes (AB-TM). AB only and TM only models were created to assess the effects of each ventricular gradient on VT dynamics. VTs were induced in all models via rapid pacing. Results: Ten baseline VTs were induced. VT inducibility in AB-TM models was not significantly different from baseline (p>0.05). Re-entry pathways in AB-TM models were different than baseline pathways due to alterations in the location of conduction block (p<0.05). VT exit sites in AB-TM models were different than baseline VT exit sites (p<0.05). VT inducibility of AB only and TM only models were not significantly different than that of baseline (p>0.05) or AB-TM models (p>0.05). Re-entry pathways and VT exit sites in AB only and TM only models were different than in baseline (p<0.05). Lastly, repolarization gradients uncovered multiple VT morphologies with different re-entrant pathways and exit sites within the same structural, conducting channels. Conclusion: VT inducibility was not impacted by the addition of apicobasal and transmural repolarization gradients, but the VT re-entrant pathway and exit sites were greatly affected due to modulation of conduction block. Thus, during ablation procedures, physiological and pharmacological factors that impact the ventricular repolarization gradient might need to be considered when targeting the VTs.